Age at death and comorbidity of dementia-related disorders among individuals with autism spectrum disorder. Issue 4 (26th September 2019) - Barnard-Brak, Lucy; Richman, David; Yang, Zhanxia
Abstract : Purpose: Autism spectrum disorder (ASD) is a lifelong disorder that requires intervention and support services for a growing geriatric population. The purpose of this paper is to examine the mean age at death of individuals with ASD and subsequent comorbidity with Alzheimer's disease, and any form of dementia, as a whole and according to sex. Design/methodology/approach: Data consisted of 1, 754 individuals who had an ASD listed as one of the causes of deaths from the National Vital Statistics System with data from 1999 to 2015. In the current study, the authors present contradictory results with a mean age at death for individuals with ASD was 68 years by adjusting for changing prevalence rates. Findings: Females with ASD had a higher mean age at death than males with ASD; consistent with the trend in the sex differences in the general population. The results of the current study also indicate that individuals with ASD were, in fact, less likely than the general population to have Alzheimer's disease or a form of dementia. However, males with ASD were significantly more likely to have acquired Alzheimer's disease or a form of dementia as compared to females with ASD. Originality/value: Guan and Li (2017) reported a mean age at death of 36 years old for individuals with ASD, which was subsequently reported in the mass media, most notably CNN. The authors contend that this study provides a more accurate estimate mean age at death.